DEVELOPMENT AND FEASIBILITY OF "TUKI": AN ANDROID-BASED EDUCATIONAL APPLICATION FOR CHILD GROWTH AND DEVELOPMENT SCREENING - Novita M Kana Wadu; Sondang Ratnauli Sianturi (Jurnal Ilmiah Keperawatan, 2026)
Background: The first five years of life represent a golden age for optimal child growth and brain development. Inadequate stimulation during this critical period can lead to permanent developmental delays across multiple domains, including motor, language, cognitive, and social skills, necessitating accessible screening solutions. Purpose: This study aimed to develop and evaluate the user-perceived quality of the "TUKI" (Tumbuh Kembang Anak Indonesia) Android-based application as an educational medium for child growth and development screening. Methods: This study used a Research and Development design based on the ADDIE framework. A total of 30 mothers of toddlers in an urban primary healthcare catchment area in Jakarta were recruited using purposive sampling. The application was developed using child growth monitoring and developmental pre-screening features based on growth charts and the Developmental Pre-Screening Questionnaire. Application quality was assessed using the Mobile App Rating Scale (MARS), and data were analysed using descriptive statistics and Pearson Product-Moment correlation test. Results: The results demonstrated an excellent overall quality score of 4.34 (SD=0.59). All individual dimensions scored consistently in the 'excellent' category: engagement (M=4.53, SD=0.49), aesthetics (M=4.39, SD=0.63), information quality (M=4.29, SD=0.62), functionality (M=4.25, SD=0.62), and subjective quality (M=4.24, SD=0.61). Pearson analysis indicated significant positive correlations among all dimensions (p<0.01). Conclusion: The TUKI application demonstrated excellent user-perceived quality and is feasible as a supportive digital educational tool for mothers in monitoring child growth and development. Paediatric and community health nurses may use this application to strengthen family-centered care and digital health literacy.